Hexanes as Deterrents in Tribolium - Hamblin, Matt; Phillips, Thomas W. (My University, 2017)
Red flour beetles are a serious pest to stored grain crops (United States 2015). Many different studies have been and are currently being done to find new anti-feedant deterrents to keep these beetles from infesting or destroying grain stores. I opted to study hexane compounds because hexane extracts significantly indicate antifeedant activity (Rajopadhye et al. 2016). Ethanol extracts have also shown to be useful anti-feedant deterrents (Khan et al 2016). Through my study, I found that a significant number of red flour beetles avoided most of the hexane compounds tested. While it is currently unknown how these compounds would react as long-term deterrents, it has been shown that some of the tested compounds do have the potential to be at least a short term deterrent.
Citation: Hamblin, M. (2017). Hexanes as Deterrents in Tribolium . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.